Pemanfaatan Kredit Usaha Rakyat (KUR) oleh UMKM dalam Pengembangan Usaha di Pasar Pantai Kelurahan Malabero - Ganefi; Fitriyah, Nurhani (RechtJiva, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in Indonesia's economy, yet MSME actors in the Pasar Pantai area of Malabero Sub-district, Bengkulu City, continue to face capital constraints and low utilization of the People's Business Credit (Kredit Usaha Rakyat/KUR) as a formal financing source. This study aims to analyze the level of KUR utilization among MSME actors in the area and identify the factors influencing its implementation from a legal perspective. The research applies an empirical legal research method with a socio-legal approach, using interviews and observation of MSME actors as primary data, combined with library research as secondary data, analyzed descriptively and qualitatively. Findings show that KUR utilization remains suboptimal, as most actors still rely on personal capital. This is driven by low financial literacy, limited understanding of credit procedures, negative perceptions of bank loans, and insufficient outreach from distributing institutions. The findings confirm that barriers to KUR implementation stem more from policy implementation (law in action) than from the regulatory substance itself (law in books), indicating that strengthening financial literacy and sustained mentorship is needed to improve KUR's effectiveness as an economic empowerment instrument for coastal MSMEs.